Early‐Stage Extratropical Cyclones' Mechanisms Over South America: RCM Added Value and Future Changes in a Warmer Planet - Gramcianinov, Carolina B.; Cardoso, Andressa A.; Silva, Natália P.; Luna‐Niño, Rosa; Castillo, Natalia; Cavazos, Tereza; Rocha, Rosmeri P. (International journal of climatology, 2025)
ABSTRACT Regional climate models (RCMs) from the CORDEX enable further investigations of the regional aspects of climate change impacts in South America. Here, we assess the CORDEX‐RCMs' present and future projections of extratropical cyclones, focusing on their frequency, early‐stage synoptic features, and added value relative to the global climate models (GCMs). Cyclones were tracked using a common algorithm in the present (1985–2005) and future RCP8.5 scenarios (2080–2099). ERA5 reanalysis was used as reference data in the present climate. Both GCMs and RCMs can identify the three major cyclone hot spots in South America: Argentina (ARG), La Plata Basin (LPB), and the south‐southeast Brazilian coast (SBR). RCMs improve GCMs' representation of the cyclogenesis frequency, adding value by decreasing the biases (~10%). Early‐stage cyclone synoptic structure also indicates RCMs' improvement of the low‐level fields by presenting mesoscale structures of warm/cold advection and moisture flux convergence/divergence in greater agreement with ERA5 (except for moisture flux divergence for LPB). RCMs and GCMs project a general decrease in cyclogenesis for the end of the century. For the cyclogenesis cores, GCMs' and RCMs' projections agree on the trend signals in SBR, LPB, and ARG in austral winter and disagree in ARG in austral summer. For LPB and SBR cyclogenesis, the RCMs and GCMs suggest a future increase in moisture flux convergence and warm advection at low levels, while a decrease in upper level divergence is projected. This indicates a reinforcement of cyclogenesis (negative sea‐level pressure trend) in the future due to the low‐level features and associated diabatic processes. For ARG, the future trends in the mean structure of cyclogenesis are relatively weak. Following other studies, cyclogenesis frequency may decrease; however, changes could occur in some important physical processes, such as low‐level moisture flux convergence and warm advection, suggesting more intense events in the future. The extratropical cyclogenesis in South America is projected to present weaker upper level forcing, in contrast to stronger low‐level mechanisms related to diabatic processes. These changes are related to the general decrease in the total number of cyclones in the region and an intensification of the systems in the future, respectively.